The Contribution of Leg Length, Leg Flexibility and Leg Speed to the Results of Kedeng Sepaktakraw's Smash Ability - Andre Febrianto; Sulaiman Sulaiman; Taufik Hidayah (STKIP Muhammadiyah Kuningan, 2022)
Smash kedeng sepaktakraw owned by players is not good, so the smash ball is often not directed and stuck in the net. This study aimed to analyze the contribution of leg length, leg flexibility, and foot speed to the kedeng smash ability of extracurricular male students of SMPN 2 Mandiraja Banjarnegara. This study uses regression and correlational methods or the contribution of four variables. The sample used was 30 male extracurricular takraw students at SMPN 2 Mandiraja. The independent variables in thiSmash kedeng sepaktakraw owned by players is not good, so the smash ball is often not directed and stuck in the net. This study aimed to analyze the contribution of leg length, leg flexibility, and foot speed to the kedeng smash ability of extracurricular male students of SMPN 2 Mandiraja Banjarnegara. This study uses regression and correlational methods or the contribution of four variables. The sample used was 30 male extracurricular takraw students at SMPN 2 Mandiraja. The independent variables in this study were leg length, limb flexibility, and foot speed, while the dependent variable was smashed kedeng. The instruments used are tests and measurements. The data analysis technique used multiple regression analysis. The results showed: 1) the length of the legs contributed to the smash kedeng by 10.24%. 2) limb flexibility contributed to the kedeng smash by 28.84%. 3) foot speed contributed to the kedeng smash by 21.16%. 4) Leg length and limb flexibility contributed to the kedeng smash by 31.36%. 5) Leg length and foot speed contributed to the kedeng smash by 35. 6) leg flexibility and foot speed contributed to the kedeng smash by 44.49%. 7) Leg length, leg flexibility, and foot speed contributed to the kedeng smash by 47%. There is a contribution from each independent variable, namely leg length, flexibility, and speed, to the dependent variable, namely the kedeng smash in sepak takraw. Physical activity and regular and structured exercises also play an essential role in the ability to smash kedeng in the sepak takraw game.s study were leg length, limb flexibility, and foot speed, while the dependent variable was smashed kedeng. The instruments used are tests and measurements. The data analysis technique used multiple regression analysis. The results showed: 1) the length of the legs contributed to the smash kedeng by 10.24%. 2) limb flexibility contributed to the kedeng smash by 28.84%. 3) foot speed contributed to the kedeng smash by 21.16%. 4) Leg length and limb flexibility contributed to the kedeng smash by 31.36%. 5) Leg length and foot speed contributed to the kedeng smash by 35. 6) leg flexibility and foot speed contributed to the kedeng smash by 44.49%. 7) Leg length, leg flexibility, and foot speed contributed to the kedeng smash by 47%. There is a contribution from each independent variable, namely leg length, flexibility, and speed, to the dependent variable, namely the kedeng smash in sepak takraw. Physical activity and regular and structured exercises also play an essential role in the ability to smash kedeng in the sepak takraw game.